2015
DOI: 10.1097/nmc.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Preterm Infant Massage

Abstract: Massage therapy could be a comforting measure for infants in the NICU to improve weight gain and enhance mental development. However, the high heterogeneity, the weak quality in some studies, and the lack of a scientific association between massage and developmental outcomes preclude making definite recommendations and highlight the need for further RCTs to contribute to the existing body of knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 19 publications
2
15
0
5
Order By: Relevance
“…Further, as reported in that review, better developmental scores and immune function were also noted in several longitudinal studies on preterm infants who had been given the Field et al [8] moderate pressure massage protocol [8]. Similarly, in a meta-analysis on 34 preterm infant massage studies conducted in many countries, the massaged preterm newborns averaged significantly greater weight gain (20 versus 16 g per day) and a shorter hospital stay (27 versus 31 days) [9]. Once again, the moderate pressure Field et al [8], (1986) protocol was used in these studies.…”
Section: Preterm Newborn Massage Therapymentioning
confidence: 69%
“…Further, as reported in that review, better developmental scores and immune function were also noted in several longitudinal studies on preterm infants who had been given the Field et al [8] moderate pressure massage protocol [8]. Similarly, in a meta-analysis on 34 preterm infant massage studies conducted in many countries, the massaged preterm newborns averaged significantly greater weight gain (20 versus 16 g per day) and a shorter hospital stay (27 versus 31 days) [9]. Once again, the moderate pressure Field et al [8], (1986) protocol was used in these studies.…”
Section: Preterm Newborn Massage Therapymentioning
confidence: 69%
“…Overall the evidence remains weak, mainly due to small sample sizes, heterogeneity and poor methodology in some studies. The current level of evidence does not support wider use of infant massage without further research [17, 39]. Two key aspects of infant massage as an early intervention have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…As a complementary and alternative medicine, massage therapy benefits the body in a way that is quick, easy, and inexpensive. It was reported that paediatric massage therapy has been used for treating diseases in children for thousands of years [51]. In recent years, many physicians have reported that paediatric massage therapy can effectively improve the function of the spleen and stomach by stimulating some specific acupoints [19, 49].…”
Section: Discussionmentioning
confidence: 99%